2002
DOI: 10.1002/jnr.10319
|View full text |Cite
|
Sign up to set email alerts
|

Two separate domains in the golli myelin basic proteins are responsible for nuclear targeting and process extension in transfected cells

Abstract: The golli products of the myelin basic protein (MBP) gene are expressed in neurons and oligodendrocytes (OLs). In certain neuronal populations, golli proteins undergo translocation between the nucleus and cytoplasm/ processes during development. The proteins consist of two domains, a golli domain of 133 amino acids and an MBP domain of variable length. One objective of this study was to identify the sequences responsible for nuclear targeting. Site-directed mutagenesis and deletion analyses were used to genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 64 publications
(65 reference statements)
4
50
0
Order By: Relevance
“…After growing for 21 d in vitro, the cells were rinsed briefly in PBS and fixed in 4% buffered paraformaldehyde for 30 min at room temperature. After rinsing in PBS, the cells were permeabilized with 0.1% Triton X-100 in PBS for 10 min at room temperature and then processed for immunocytochemistry following the protocol as outlined by Reyes et al (2002). Essentially, fixed cells were incubated in a blocking solution (5% goat se-rum in PBS) followed by an overnight incubation at 4°C with a polyclonal antibody for MBP (1:700).…”
Section: Analysis Of the Golli Ko Transgenic Micementioning
confidence: 99%
See 1 more Smart Citation
“…After growing for 21 d in vitro, the cells were rinsed briefly in PBS and fixed in 4% buffered paraformaldehyde for 30 min at room temperature. After rinsing in PBS, the cells were permeabilized with 0.1% Triton X-100 in PBS for 10 min at room temperature and then processed for immunocytochemistry following the protocol as outlined by Reyes et al (2002). Essentially, fixed cells were incubated in a blocking solution (5% goat se-rum in PBS) followed by an overnight incubation at 4°C with a polyclonal antibody for MBP (1:700).…”
Section: Analysis Of the Golli Ko Transgenic Micementioning
confidence: 99%
“…They have been found to be expressed during embryonic development in neuronal populations during process extension and migration (Landry et al, 1998). Overexpression of golli induces a striking morphological effect on enhanced process and sheet elaboration in OL cell lines (Reyes and Campagnoni, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Golli proteins first appear in many neurons when they are extending processes for migration, establishment of connections and, in the case of oligodendrocytes (OLs), before myelination (Landry et al, , 1997(Landry et al, , 1998Pribyl et al, 1996). In vitro transfection studies have shown that overexpression of golli proteins in OL cell lines can induce these cells to elaborate extensive processes and membrane sheets, adopting a morphology similar to mature OLs in culture (Reyes and Campagnoni, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that the phosphorylation status of several potential protein kinase C (PKC) phosphorylation sites within the N-terminal region of MBP may modulate their subcellular localization in OLGs [20,22,[31][32][33]45], another phenomenon worthy of further exploration.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that Golli proteins, which arise from transcription start site 1 of the same gene complex as MBP, but are expressed earlier in development, have a non-traditional nuclearlocalization signal (NLS) contained within amino acids 1-36 of the classic MBP portion (Fig. 1A) [33]. However, this non-traditional NLS encoded within exon-I of classic MBP does not cause 18.5-kDa MBP to be localized in the nucleus, and presumably is also not responsible for the localization of 21.5-kDa MBP in the nucleus.…”
Section: Introductionmentioning
confidence: 99%